The Relationship Between Teaching Style and Students’ Learning Motivation in English Subject - Anam, Samsul; Muhammad, Zakky Dausar; Anggarini, Ida Fitri; Maullidia, Rahma Asri; Fukhoma, Maslukhatis Sa’idah; Nashirin, Muhammad (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2026)
The thesis discusses a correlation between teaching style and students’ learning motivation in English. This research seeks to identify the teacher style applied and its relationship with student learning motivation at MTs N Assalam. The research question will be discussed about (1) the teaching style applied in the learning process, (2) What relationship occurs between the two variables. (3) And how significant the two variables are. This study uses the correlation method with a quantitative type. The population was 60 students in class 9A and B of MTs N Assalam Bangilan, Tuban. Data collection techniques using closed questionnaires. Descriptive analysis is used to provide an overview of each variable. Test requirements analysis in this study includes validation and reliability. The hypothesis test consists of a correlation test and coefficients together (F test). The results of this study indicate that (1) the teaching style applied by the teacher in the class is the facilitator style of 65.5%. (2) There is a positive and significant value between the teaching style and student learning motivation which is equal to 0.521. (3) While the significance value of the two variables is 0,000. As for how strong the impact of teaching style on student motivation is 64.4%. Keyword: learning motivation, teaching style.